Melanoma patient imaging in the era of effective systemic therapies. Issue 8 (August 2017) - Stodell, M.; Thompson, J.F.; Emmett, L.; Uren, R.F.; Kapoor, R.; Saw, R.P.M.
Abstract: Imaging plays a critical role in the current multi-disciplinary management of patients with melanoma. It is used for primary disease staging, surgical planning, and surveillance in high-risk patients, and for monitoring the effects of systemic or loco-regional therapies. Several different imaging modalities have been utilised in the past. Contemporary imaging practises vary geographically depending on clinical guidelines, physician preferences, availability and cost. Targeted therapies and immunotherapies have revolutionised the treatment of patients with metastatic melanoma over the last few years. With this have come new patterns of disease that were not observed after conventional therapies, and new criteria to assess therapeutic responses. In this article we review the role of imaging for patients with melanoma in the era of effective systemic therapies and discuss likely future developments.